A Toll-like Receptor-Activating, Self-Adjuvant Glycan Nanocarrier - Xie, Daping; Niu, Yiming; Mu, Ruoyu; Campos de Souza, Senio; Yin, Xiaoyu; Dong, Lei; Wang, Chunming (Frontiers in Chemistry, 2022)
The global pandemic of COVID-19 highlights the importance of vaccination, which remains the most efficient measure against many diseases. Despite the progress in vaccine design, concerns with suboptimal antigen immunogenicity and delivery efficiency prevail. Self-adjuvant carriers–vehicles that can simultaneously deliver antigens and act as adjuvants–may improve efficacies in these aspects. Here, we developed a self-adjuvant carrier based on an acetyl glucomannan (acGM), which can activate toll-like receptor 2 (TLR2) and encapsulate the model antigen ovalbumin (OVA) via a double-emulsion process. In vitro tests showed that these OVA@acGM-8k nanoparticles (NPs) enhanced cellular uptake and activated TLR2 on the surface of dendritic cells (DCs), with increased expression of co-stimulatory molecules (e.g. CD80 and CD86) and pro-inflammatory cytokines (e.g. TNF-α and IL12p70). In vivo experiments in mice demonstrated that OVA@acGM-8k NPs accumulated in the lymph nodes and promoted DCs’ maturation. The immunization also boosted the humoral and cellular immune responses. Our findings suggest that this self-adjuvant polysaccharide carrier could be a promising approach for vaccine development.